Development of a boost convertor for photovoltaic system MPPT using fuzzy logic control - Abdull Kadir, Junaini (2013)
Photovoltaic (PV) systems has received great attention in research for generating renewable energy due to its advantages over fossil based energy in terms of sustainability, environmental friendliness and price stability. However, the widespread use of PV meets several challenges such as increasing the efficiency of PV conversion. Another drawback of PV system is that it does not provide a constant energy source because its output power changes with temperature and irradiation or insulation. PV modules have unique current versus voltage characteristics. From the I-V characteristics, PV systems must be operated at a maximum power point (MPP) of specific current and voltage values so as to increase the PV efficiency. For any PV system, the output power can be increased by tracking the MPP of the PV module by using a controller connected to a boost converter. An important consideration in increasing the efficiency of PV systems is to operate the system near maximum power point (MPP) so as to obtain the approximately maximum power of PV array. To achieve maximum energy produced by a PV array, maximum power point tracking (MPPT) techniques are used. The position of the MPP is unknown but can be traced by using an MPPT To overcome this problem, Maximum Power Point Tracker DCDC